Critical archaeology in the digital age : proceedings of the 12th IEMA Visiting Scholar Conference - Garstki, Kevin (Cotsen digital archaeology series, 2022)
Every part of archaeological practice is intimately tied to digital technologies, but how deeply do we really understand the ways these technologies impact the theoretical trends in archaeology, how these trends affect the adoption of these technologies, or how the use of technology alters our interactions with the human past? This volume suggests a critical approach to archaeology in a digital world, a purposeful and systematic application of digital tools in archaeology. This is a call to pay attention to your digital tools, to be explicit about how you are using them, and to understand how they work and impact your own practice. The chapters in this volume demonstrate how this critical, reflexive approach to archaeology in the digital age can be accomplished, touching on topics that include 3D data, predictive and procedural modelling, digital publishing, digital archiving, public and community engagement, ethics, and global sustainability. The scale and scope of this research demonstrates how necessary it is for all archaeological practitioners to approach this digital age with a critical perspective and to be purposeful in our use of digital technologies.--